Preparación de películas delgadas de As2S3 por depósito químico con perspectivas de aplicación en celdas solares - Benítez Garza, Ángel Salvador; Lugo, S.; Peña Méndez, Yolanda; Elizondo Martínez, Perla; Garza, T. (Universidad Autónoma de Nuevo León, 2010)
In this paper we obtained thin films of As2S3 by chemical bath deposition. The films were prepared at a temperature of 80ºC for 3 hours each deposit. They were thermally treated at 180ºC and 250ºC for 30 minutes for 1 hour, respectively. The energy gap was calculated 2.9 eV. The conductivity was around, 3.62e-7